Lokalisering av sågverk i Västerbotten : en jämförelse mellan två alternativ - Nylund, Olle; Sundby, Johan (SLU/Dept. of Forest Resource Management, 2011)

(untitled)
The number of sawmills in Sweden has decreased dramatically since the 1980s and the trend looks set to continue. The sawmills that are left instead becomes larger and are situated farther apart. In northern Sweden, they are concentrated along the coastline. In our study, we compared conditions for running a sawmill in inland areas and coastal areas and looked at what factors have the greatest impact on the profitability of the sawmill in northern Sweden. We chose to compare different locals conditions for a sawmill that only sawn pine timber and had an annual raw material requirements of 300 000 m3ub per year. By analyzing the kNN-data from the Swedish National Forest Inventory we have taken out the size of the timber volume at each site and its catchment. We have also looked at possible competitors in the areas that may affect the purchase price of the commodity. From these data, we have been able to calculate transport distances and then compared the different available distribution channels to get the finished products on the market. Then added together and compared the various factors affecting costs and arrived at the location which is the most profitable and which factors are most instrumental to the outcome.